PENGGUNAAN SARI UMBI BAWANG MERAH DALAM PEMBIBITAN PAPAYA - Faryska Nur Ichsan; Djoko Purnomo; Linajanti Darsono (Caraka Tani: Journal of Sustainable Agriculture, 2015)
Community awareness in healthy life is increasing by consuming nutritious food through such as fruit. So it is necessary for increasing the availability of fruit either by cultivation expansion or technology development. The production life of papaya crop approximately three years only, so that replanting takes relatively fast. But there is some limitations mainly the availability of suitable seedling (age and uniformity). For improving the availability of suitable papaya seedling can be used gibberellin as growth regulator substance. But gibberellin in pure analysis limitations are expensive, not always available, and high technology in application.  The aim of the research was to test of shallot juice (1 kg of shallot bulbs destroyed by juicer) as gibberellin substitute for improving papaya seedling.  The experiment was conducted at terrace house, consist of percentage and speed of germination and growth of seedling observation after seed soaked 2 hours in shallot juice several concentration treatment. Test of the germination percentage and speed conducted for 10 seeds on pastur paper in petridish (11.5 diameter) as germination media. The experiment for growth seedling was arranged in randomized completely design which the treatments are: seed soaked in water,  soaked in 5, 10, 15, dan 20 ml l-1 shallot juice concentration, and soaked in gibberellin 10 ppm. Each of the experiment unit consist of 8 seedlings which planted on trypot (composite of plastic pots by size 5.5x5.5 cm at surface, 5.5 cm height, and 2,5x2,5 cm at the base, each of traypot consist of 32 pots). So in each of tray pot there are 8 experimental units, each of experimental unit repliclated 3 times. Traypot and petridish at terrace house shaded by woven plastic 65%, by size 2.5x1.5x2.0 m (length, width, and height). Yield of the research showed that shallot juice potential as gibberellin replacement in papaya nursery. Response of papaya seed (percentage and speed of germination) and seedling (length of root, stem diameter, number of leafs, leaf area, and weight of biomass) to 15 ml l-1 shallot juice equal with gibberellin 10 ppm.